1991
DOI: 10.1016/0378-1097(91)90594-z
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of components of the export machinery in prokaryotes

Abstract: The SecA and SecB proteins are involved in protein translocation in Escherichia coli. Immunoblot analysis was used to investigate the possible conservation of these proteins in prokaryotes. Cross-reacting proteins were detected in all other Enterobacteriaceae tested, but not in microorganisms more distantly related from Escherichia coli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…We also showed that S. marcescens SecB crossreacted strongly with E. coli SecB (see Fig. 2C), as reported previously (9). S. marcescens strain from which secB was deleted had defective pre-MBP processing.…”
Section: S Marcescenssupporting
confidence: 90%
See 1 more Smart Citation
“…We also showed that S. marcescens SecB crossreacted strongly with E. coli SecB (see Fig. 2C), as reported previously (9). S. marcescens strain from which secB was deleted had defective pre-MBP processing.…”
Section: S Marcescenssupporting
confidence: 90%
“…A SecB homolog has been identified in S. marcescens on the basis of cross-reaction of a particular species with anti-E. coli SecB antibodies (9). Conversely, the specificity of the SecB chaperone for the Sec translocation system, especially the specific interaction with SecA (14), the ATPase of the Sec translocation system, make the involvement of SecB in type I secretion all the more puzzling.…”
mentioning
confidence: 99%
“…These alleles, prlD21, -22, and -23 and azi-17, confer azide resistance, are potent enough with LamB17D-LacZ to allow SDI, and cause defects in the secretion of wild-type proteins. Strikingly, all alter Tyr-134, a residue conserved in all known SecA proteins (5,14,34,35,39,46,47,59,62). We suspect that these four mutations may slow an ATPase activity of SecA.…”
Section: Discussionmentioning
confidence: 92%
“…This discovery, together with the universal presence of signal sequences in secreted proteins, argues that the basic mechanism of protein secretion has been conserved throughout nature. While homologs of SecA have been found in other bacteria, in plastids of algae, and in chloroplasts of plants (5,14,34,35,39,46,47,59,62), none has been discovered in yeasts or mammals. Whether this reflects an important difference between prokaryotes and eukaryotes remains to be determined.…”
mentioning
confidence: 99%
“…Further (42). The existence of a Sec-like system in shigellae is suggested by the finding that polyclonal antisera to E. coli SecA and SecB recognize proteins of similar molecular masses in whole-cell protein extracts of S. flexneri and S. dysenteriae (18).…”
Section: Resultsmentioning
confidence: 99%